1993
DOI: 10.1111/j.1468-5957.1993.tb00259.x
|View full text |Cite
|
Sign up to set email alerts
|

Auditor Choice and Audit Fee Determinants

Abstract: An analytical model predicts that cross‐sectionally (1) the marginal cost of auditor quality is inversely related to the strength of client companies' internal control. (2) In the short run, clients with stronger control, lower business risk, or less complex audits choose higher quality auditors; but whether they pay higher audit fees is indeterminate. (3) In the long run, client companies have both lower quality auditors and weaker controls as risk or complexity increase, so less precise financial reporting i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 18 publications
1
17
0
1
Order By: Relevance
“…As a consequence, they propose that riskier firms will choose higher-quality audit firms because the incremental value of an audit report provided by a higher-quality audit firm increases in the riskiness of the finn. In contrast, Thornton and Moore (1992) assume that the fee market does not reward intermediaries for taking such risks. Thus, their analytical results suggest that riskier firms will choose lower-quality audit firms since the incremental benefit of a higher-quality audit firm decreases in the riskiness of the firm.…”
Section: Previous Researchmentioning
confidence: 99%
“…As a consequence, they propose that riskier firms will choose higher-quality audit firms because the incremental value of an audit report provided by a higher-quality audit firm increases in the riskiness of the finn. In contrast, Thornton and Moore (1992) assume that the fee market does not reward intermediaries for taking such risks. Thus, their analytical results suggest that riskier firms will choose lower-quality audit firms since the incremental benefit of a higher-quality audit firm decreases in the riskiness of the firm.…”
Section: Previous Researchmentioning
confidence: 99%
“…It revealed that a wide range of factors which cause the variation of audit fees are likely to be classified into five general categories; that is, audit workload, complexity, risks, auditee's inputs and the size of accounting firm. Thornton and Moore (1993) provided a similar classification in which the audit fee determinants were divided into four groups; client company size, weakness of internal control, business risk and audit complexity.…”
Section: Introductionmentioning
confidence: 99%
“…Starting with Simunic (1980) there has been much debate on whether some auditors earn premium fees and what the source of the premium is (Thornton and Moore, 1993). By appealing to the economic theory of quality differentiation, higher fees (to some auditors) are consistent with a quality premium and represent a return to an auditor's costly investment in quality.…”
Section: Introductionmentioning
confidence: 98%